Association between serum cystatin C level and cognition in older adults: a cross-sectional analysis - Wang, Shuli; Lin, Xuechun; Zhou, Jie; Li, Meng; Song, Dan (Frontiers in Neuroscience, 2023)
Introduction Serum Cystatin C level, an indication of kidney function, has been implicated in the pathogenesis of Alzheimer’s disease and cognitive impairment. In this cross-sectional study, we looked into the relation between serum Cystatin C levels and cognition in a group of U.S. older adults. Method The data of this study were from the National Health and Nutrition Examination Survey (NHANES) 1999–2002. A total of 4,832 older adults aged ≥60 who met the inclusion criteria were included. The Dade Behring N Latex Cystatin C assay, which is a particle-enhanced nephelometric assay (PENIA), was utilized to assess Cystatin C levels in participants’ blood samples. Participants’ cognition was examined using the digit symbol substitution test (DSST). Z-scores of the DSST were calculated based on sample means and standard deviations (SD). To investigate the relationships between the quartiles of serum Cystatin C level and DSST z scores, multiple linear regression models were developed while controlling for age, sex, race/ethnicity, and education. Results The average age of the participants was 71.1 (SD 7.8). The participants were about half female (50.5%), non-Hispanic White (61.2%), and (36.1%) who had completed at least some college. They had an average serum Cystatin C level of 1.0 mg/dl (SD 0.44). After performing multiple linear regression with a reference group consisting of participants in quartile one of plasma Cystatin C levels, we found that serum Cystatin C levels in quartiles three and four were independently associated with lower DSST z scores (β = −0.059, 95% CI −0.200 to −0.074 and β = −0.108, 95% CI −0.319 to −0.184, respectively). Conclusion Higher serum Cystatin C level is associated with worse processing speed, sustained attention, and working memory in older adults. Cystatin C level may be a biomarker for cognitive decline in older adults.